A Complex Array of Proteins Related to the Multimeric Leucine Aminopeptidase of Tomato. - Gu, Y. Q. (1996)
Leucine aminopeptidase (LAP) mRNAs are induced in response to mechanical wounding, pathogen infection, and insect infestation (V. Pautot, F.M. Holzer, B. Reisch, L.L. Walling [1993] Proc Natl Acad Sci USA 90: 9906-9910). Polyclonal antibodies to a glutathione S-transferase-LAP fusion protein and affinity-purified antibodies recognizing LAP antigenic determinants detected four classes of polypeptides in tomato (Lycopersicon esculentum) leaves. All four classes had multiple polypeptides in two-dimensional polyacrylamide gel electrophoresis immunoblots. Although antigenically related to the wound-induced tomato LAP proteins, the 77- and 66-kD LAP-like proteins accumulated in both healthy and wounded leaves. Two classes of 55-kD polypeptides with distinctive isoelectric points were designated as plant LAPs; only the acidic LAP proteins accumulated to high levels after mechanical wounding or Pseudomonas syringae pv tomato infection of tomato leaves. The temporal accumulation of LAP mRNAs was correlated with the increase in acidic LAP protein subunits. A slow-migrating LAP activity was detected using a native gel assay after wounding. The molecular mass of the native wound-induced LAP enzyme was 353 kD. The 55-kD acidic LAP proteins were associated with induced LAP activity, whereas the neutral LAPs and the LAP-like proteins were not associated with this exopeptidase. A second, fast-migrating aminopeptidase was detected in both healthy and wounded tomato leaves. Cell fractionation experiments revealed that wound-induced LAP is a soluble enzyme.